Atravessamento de saberes nos estudos sobre a linguagem no/do Brasil nos anos 50 - Schneiders, Caroline Mallmann (2011)
The issue of research on which we focus this study is based on a reflection around the discourse about linguistic knowledge production in/of Brazil in the fifties. Our central scope is in the understanding of temporality and discursive memory that constitute the scientific discourse about language of this conjuncture from the crossing of Linguistics disciplinary field knowledge. We are interested in this crossing, as it refers to a domain not yet institutionalized in the academic Brazilian context and because it was in a period that there were advances in studies around the Portuguese of Brazil. Thus, in our research, it was approached issues that emphasizes how and for to the scientific discourse around language features a combination with knowledge from different fields; seeking to examine, in particular, the operation of the crossing of Knowledge on Linguistics in this discourse, this crossing can be understood through the notion of transverse-speech (cf. Pêcheux, 2009 [1988]). In order to do that, we have as object of study two works by Serafim da Silva Neto: Introdução ao Estudo da Língua Portuguêsa no Brasil, 1st edition, 1950, and Introdução ao Estudo da Filologia Portuguêsa, 1st edition, 1956, which are significant to the situation in question, by inserting at two different times in the 50s. The first one is recognized as the best work about the Portuguese of Brazil, and the second one is considered a guide that was circulated in Language Courses at the time in question (cf. Penha, 2002). In this sense, we wrote in the view of History of Linguistic Ideas, linking it to theoretical and methodological principles of Discourse Analysis from French orientation, as it is developed in Brazil.